The Influence of Discounts and Brand Awareness Mediated by Buying Intention on the Buying Decision of Domino's Pizza Products - Paniroi, Henry Fransisko (Universitas Mercu Buana, 2025)
This research aims to analyze the effects of Discounts and Brand Awareness on consumer Buying Decisions at Domino's Pizza in Bekasi Regency, with Buying Intention as a mediating variable. Using the Partial Least Square analysis method, the results show that both Discounts and Brand Awareness significantly influence Buying Decisions, both directly and through Buying Intention. These findings underscore the importance of promotional strategies focusing on discounts and enhancing brand awareness to improve consumer satisfaction and loyalty. This research provides new insights for the company in designing more effective marketing strategies.